Shadow Removal Based on Gamma Decoding Method for Moving Object Images - Hasanuddin Al-Habib; Budi Setiyono (LPPM Institut Teknologi Sepuluh Nopember, 2018)
Shadows are reflections of objects exposed to light. So there is an image pixel that has a darker intensity than the object’s pixel. The development of digital technology, the shadow into noise on digital images and digital video. Therefore, the information on the image becomes inaccurate. One of the usage of digital image or video digital is intelligent transportation system using digital video-based CCTV camera. But the use of digital video has several problems, including the presence of a shadow. Therefore, it is necessary to have a method to eliminate shadows. In this paper, we use gamma decoding method to determine object pixels and pixel shadow based on the illumination of the object, so the shadow pixels can be eliminated. The result of this research is images without shadow.